Centering Group Treatment for Women With Interstitial Cystitis/Bladder Pain Syndrome: A Prospective, Parallel-Group Cohort Study. Issue 4 (21st April 2023) - Meriwether, Kate V.; Ravichandran, Niharika; Darley, Cassandra J.; Panter, Virginia; Komesu, Yuko M.
Abstract : Importance: Women with interstitial cystitis/bladder pain syndrome (ICBPS) face isolation and treatment challenges. Group medical visits using Centering models have successfully treated other conditions but have not been explored in ICBPS. Objective: This study aimed to describe ICBPS pain and symptom control comparing standard treatment alone versus standard treatment augmented with Centering visits. Study Design: This prospective cohort study recruited women with ICBPS receiving standard care (control) or standard care augmented with group Centering. We administered validated questionnaires at baseline and monthly for 12 months. The primary outcome was change in the pain numerical rating scale, with Patient-Reported Outcomes Measurement Information System Pain Interference Scale and Bladder Pain/Interstitial Cystitis Symptom Score change as secondary measures. Results: We enrolled 45 women (20 Centering, 25 controls). Centering had significantly better numerical rating scale pain scores at 1 month (mean difference [diff], −3.45) and 2 months (mean diff, −3.58), better Patient-Reported Outcomes Measurement Information System Pain Interference Scale scores at 1 month (mean diff, −10.62) and 2 months (mean diff, −9.63), and better Bladder Pain/Interstitial Cystitis Symptom Score scores at 2 months (mean diff, −13.19), and 3 months (mean diff, −12.3) compared with controls. In modeling, treatment group (Centering or control) and educational levels were both associated with all the outcomes of interest. Beyond 6 months, there were too few participants for meaningful analyses. Conclusions: Women with ICBPS participating in a Centering group have, in the short term, less pain, pain interference, and ICBPS-specific symptoms than patients with usual care alone. Larger studies with more follow-up are needed to determine if this treatment effect extends over time.